Conversion disorder with psychogenic vomiting and coexisting organic etiology in an adolescent: A case report - Tanbir Ahmed; Sifat E Syed; Afsana Benta Anowar; Syeda Rawnak Jahan; Nahid Mahjabin Morshed (Bangabandhu Sheikh Mujib Medical University Journal)
Not applicable